The Increasing Importance of Administrative Practices in the Shaping of the Welfare State - Staffan Blomberg; Jan Petersson (Social Work & Society, 2011)
In this article we analyse changes in the Swedish welfare state through the example of the municipal social care services for older persons. It is shown that one can trace a transformation to three different processes (layers) of change. When looked upon as complementary phenomena they show why and how administrative practices have become the dominant locus in the re-shaping of the welfare state. The incorporation of managerialism as the prevailing mode for delivering the services and organizing social policy leads to the main conclusion, that we are witnessing the move away from a moral/political to an administrative welfare regime. In the ending paragraph, we argue that this move weakens social citizenship and transfers values and principles in social policy to the administrative sphere. We further argue that this focus has some broader implications in characterizing and analyzing cross-national differences as to welfare regimes.